IDENTIFYING AN ORGANIZATIONAL CULTURE MODEL/FRAMEWORK TO EFFECTIVELY APPROACH QUALITY MANAGEMENT: A COMPREHENSIVE LITERATURE REVIEW - Buhumaid, Maitha (International Journal For Research In Business, Management And Accounting, 2022)
Quality management (QM) is neither a new concept nor a set of processes or practices. Nonetheless, with rapid global changes across industries and markets, implementing effective QM practices has been more urgent than ever before. Implementing QM practices in any firm or company cannot occur in isolation from the organizational culture of this specific firm or company. There are several models and frameworks that address organizational culture, the most popular of which are the competing values framework (CVF), the Denison model, the organizational culture inventory (OCI), and the organizational culture profile (OCP). The challenge for many researchers is which of these models/frameworks they should use in approaching organizational culture. This paper provides a comprehensive literature review informed by the results of a Boolean search about each of these models/frameworks. This enabled the study to compare and contrast each one of them, providing a set of recommendations and future directions for researchers in this area.